2018
DOI: 10.3389/fphar.2018.00977
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone, a PPAR-γ Activator, Stimulates BKCa but Suppresses IKM in Hippocampal Neurons

Abstract: Pioglitazone (PIO), a thiazolidinedone, was reported to stimulate peroxisome proliferator-activated receptor-γ (PPAR-γ) with anti-inflammatory, anti-proliferative, anti-diabetic, and antidepressive activities. However, whether this compound exerts any perturbations on Ca2+-activated K+ and M-type K+ currents in central neurons remains largely unresolved. In this study, we investigated the effects of PIO on these potassium currents in hippocampal neurons (mHippoE-14). In whole-cell current recordings, the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…The activity of BK Ca channels has been reported to be present in mHippoE‐14 neurons (Chen et al, ). Morphine‐induced hyperalgesia has been demonstrated to be linked to the increase in BK Ca ‐channel activity (Hayashi et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The activity of BK Ca channels has been reported to be present in mHippoE‐14 neurons (Chen et al, ). Morphine‐induced hyperalgesia has been demonstrated to be linked to the increase in BK Ca ‐channel activity (Hayashi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, subsequent addition of pioglitazone (10 μM) on the intracellular surface of the excised patch increased the probability of BK Ca ‐channel openings to 0.029 ± 0.008 ( n = 8, p < .05). Pioglitazone has been reported to activate BK Ca channels (Chen et al, ; Hung, Chu, Wu, Wu, & Huang, ). However, in this study, NAL was found to be unable to modify the activity of BK Ca channels in mHippoE‐14 neurons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A noise‐like outward current of BK Ca channel was evoked in the primary cultured rat hippocampal neurons. This is in agreement with a previous study in the embryonic mouse hippocampal neurons . In the range of 33.3–300 mg/l, TFR significantly increased the current of neuronal BK Ca channel in a concentration‐dependent manner, which could be inhibited by IBTX, a specific blocker of BK Ca channel.…”
Section: Discussionmentioning
confidence: 99%